Cultural and Moral Values in East Javanese Folklore - Mamik Tri Wedawati; Fithriyah Inda Nur Abida; Much. Koiri; Adam Damanhuri (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The study aims to present the cultural and moral values of East Javanese Folklore. This research used a qualitative research with documentation technique. The object of the study were two selected stories from East Java, namely Sura and Baya and Banyuwangi stories. The study of cultural and moral values is based on the Koentjaraningrat classification which defines the diversity of values that exist in human life. The result shows that the stories contain many traditional and cultural values that are full of moral messages. Through the theme and characterization, the philosophical values and attitudes of the community are well portrayed. The stories also reveal that the cultural values influence the character and personality of the Javanese people.